2021
DOI: 10.1101/2021.08.24.457536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinically-relevant T cell expansion protocols activate distinct cellular metabolic programs and phenotypes

Abstract: Ex vivo expansion conditions used to generate T cells for immunotherapy are thought to adopt metabolic phenotypes that impede therapeutic efficacy in vivo. The comparison of five different culture media used for clinical T cell expansion revealed unique optima based on different output variables including proliferation, differentiation, function, activation and mitochondrial phenotypes. T cells adapted their metabolism to match their media expansion condition as shown by glucose and glutamine uptake, and patte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Finally, T cells were expanded in the presence of phosphoinositide 3-kinase inhibitor (PI3K) to enrich for memory T cells in an ongoing BCMA CAR-T clinical trial which is reported to show promising signs of improved efficacy ( 96 ). Even the choice of media can have a major impact on the function and metabolism of the T cells ( 97 ). Work in NK cells has been carried out to examine the impact of changing feeder cells used for expansion, and how this can affect metabolic fitness and cytotoxicity ( 98 , 99 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, T cells were expanded in the presence of phosphoinositide 3-kinase inhibitor (PI3K) to enrich for memory T cells in an ongoing BCMA CAR-T clinical trial which is reported to show promising signs of improved efficacy ( 96 ). Even the choice of media can have a major impact on the function and metabolism of the T cells ( 97 ). Work in NK cells has been carried out to examine the impact of changing feeder cells used for expansion, and how this can affect metabolic fitness and cytotoxicity ( 98 , 99 ).…”
Section: Introductionmentioning
confidence: 99%